Pedagogical Approaches for an Effective Classroom Management - Narayan Prasad Adhikari (Interdisciplinary Research in Education, 2021)
This study aimed to find out the pedagogical approaches for effective classroom management. The study is also undertaken to explore the teacher's opinions on effective classroom management. The study has addressed the research question ''how teachers can effectively manage a classroom with a wide range of learning abilities and styles, in a student-centered way''. It is adopted the qualitative research design. Qualitative data were taken from in-depth interviews. Thematic analysis and verbatim analysis have been done. Data were analyzed on the themes of student-centered classroom management, reactive and proactive classroom management strategies, cooperative discipline, culturally responsive teaching teacher’s role, and classroom management. The study's findings entail that a well-managed classroom is a powerful motivator for students’ learning. Reactive and proactive classroom, cooperative and collaborative learning atmosphere, culturally responsive teaching and learner-friendly teaching by the teacher, has been identified as the pedagogical approaches for effective classroom management. Based upon the findings, it can be suggested that the school principals should constantly organize seminars and workshops for teachers to get them aware of effective classroom-management techniques. The study further implies a constant need to introduce and use new-classroom-management behaviors from the side of teachers.